IMPROVING STUDENTS’ SPEAKING ABILITY BY USING SYNCHRONOUS COMMUNICATION STRATEGY - Ratu Yulianti Natsir (Universitas Muhammadiyah Makassar, 2016)
The objective of the research was to find out the improvement students’ speaking ability by using Synchronous Communication strategy at the second grade of SMA 1 Mappakasunggu. This research used Classroom Action Research that consisted two cycles. The research population was the second grade of SMA 1 Mappakasunggu academic year 2014/2015. The sample of this research consisted of 27 students. The researcher obtained the data by using speaking test and observation sheet. The findings of the student's speaking test in cycle I and cycle II had significantly different scores. There was a better increase of gains by students at the end of action of the second cycle. The research findings indicated that the application of Synchronous Communication strategy was significant in improving the students’ speaking ability of accuracy which focused on vocabulary and fluency which focused on self-confidence. It was proved by the mean score of diagnostic test was 4.5 that classified poor, the improving in cycle 1 was 6 that classified fair and cycle 2 was 7 that classified good. It means that there was the improvement of the students’ speaking ability in SMAN 1 Mappakasunggu.Keywords: Speaking Ability, Synchronous Communication Strategy